LAG3 is not expressed in human and murine neurons and does not modulate α‐synucleinopathies - Marc Emmenegger; Elena De Cecco; Marian Hruska‐Plochan; Timo Eninger; Matthias M Schneider; Melanie Barth; Elena Tantardini; Pierre de Rossi; Mehtap Bacioglu; Rebekah G Langston; Alice Kaganovich; Nora Bengoa‐Vergniory; et al. (EMBO Molecular Medicine, 2021)
Abstract While the initial pathology of Parkinson’s disease and other α‐synucleinopathies is often confined to circumscribed brain regions, it can spread and progressively affect adjacent and distant brain locales. This process may be controlled by cellular receptors of α‐synuclein fibrils, one of which was proposed to be the LAG3 immune checkpoint molecule. Here, we analysed the expression pattern of LAG3 in human and mouse brains. Using a variety of methods and model systems, we found no evidence for LAG3 expression by neurons. While we confirmed that LAG3 interacts with α‐synuclein fibrils, the specificity of this interaction appears limited. Moreover, overexpression of LAG3 in cultured human neural cells did not cause any worsening of α‐synuclein pathology ex vivo. The overall survival of A53T α‐synuclein transgenic mice was unaffected by LAG3 depletion, and the seeded induction of α‐synuclein lesions in hippocampal slice cultures was unaffected by LAG3 knockout. These data suggest that the proposed role of LAG3 in the spreading of α‐synucleinopathies is not universally valid.